Science Teacher Technology Acceptance Model On Zoom Cloud Meeting Application - Azmi, Khairul; Zamista, Adelia Alfama; Sholihat, Neng (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The purpose of this study was to see the acceptance of science teachers to the use of zoom in carrying out learning in accordance with the nature of science within the framework of the technology acceptance model. This research is a quantitative research with data analysis techniques using descriptive techniques and path analysis. The research population was 34 science teachers who were members of the science teacher association (PPII) in the Riau region, with a sample of 27 teachers who used zoom when teaching. The variables studied in this study were selected from 4 variables from the TAM framework, namely: perceived usefulness (PU), perceived ease of use (PEOU), behavioral intention to use (BIU) and, actual technology use (ATU). The results of the study show that the teacher's perception of zoom is seen by the PU, PEOU, and BIU variables in the high category, because zoom is easy to use and can facilitate the implementation of learning in accordance with the nature of science. While the ATU in the low category is due to the influence of other factors such as the network. Path analysis showed a significant relationship between the following variables: 1) PEOU and PU, 2) PU and BIU, 3) PEOU and BIU, and 4) BIU and ATU.